Land evaluation and site assessment for the basic farmland protection in Lingyuan County, Northeast China. (10th September 2021) - Qian, Fengkui; Lal, Rattan; Wang, Qiubing
Abstract: With respect to the stability and permanence of basic farmland, the LESA system provides a scientific theory and reference method for farmland protection. In this study, the land evaluation and site assessment (LESA) system, widely tested and applied for farmland protection in the U.S., was introduced in Lingyuan County, Northeast China. The research results showed that the LESA system had apparent advantages in fully evaluating farmland soil quality and site conditions and achieved scientific zoning protection for basic farmland. Six soil factors and five site condition factors were used to construct the land evaluation (LE) and site assessment (SA) subsystems, and the calculated ratio (6:4) of the LE and SA subsystems rationally indicated that LE was the superior subsystem and the essential basis for crop production and agriculture use, which also coincided with the practical characteristics of farmland utilization and protection in Lingyuan County. Four farmland protection and utilization zones were developed: the basic farmland zone, the potential basic farmland zone, the ecological restoration zone and the construction reservation zone. Finally, 60.35% of the farmland was demarcated as basic farmland area, which can not only guarantee farmland stability and permanence but also provide scientific guidance for construction occupation and ecological restoration. The abundant experience of LESA applications in U.S. counties provides a valuable reference for farmland protection in the counties of China. Highlights: The LESA system was first introduced and applied to farmland evaluation and protection in Lingyuan County, Northeast China. The final ratio 6:4 between LE and SA subsystems represented its variability and flexibility for farmland conditions. The final LESA results proved its suitability and scientificity in the basic farmland protection.